Development of m-learning in flipped classroom learning model to increase interest and understanding of mathematics concepts - Isti Qama Damayanti; Deni Hardianto (Jurnal Inovasi dan Teknologi Pembelajaran, 2025)
Mathematics education in Indonesia faces challenges of low learning interest and limited conceptual understanding among students, reflected in Indonesia's 2022 PISA score of 366 points. This research aims to develop M-learning based on flipped classroom model to enhance students' interest and understanding of mathematical concepts. The research method employed the ADDIE model, with SDLC approach specifically applied in the development phase. Research subjects involved 69 eleventh-grade students from SMA Negeri 1 Cawas. Data collection instruments included expert validation questionnaires, user response questionnaires, learning interest questionnaires, and mathematical concept understanding tests. Results showed M-learning was highly feasible according to media expert validation (average 3.84) and material expert validation (average 3.9), rated as very practical by teachers (average 3.96) and practical by students (average 3.36). M-learning implementation increased learning interest by 20.2% and mathematical concept understanding by 72.70%. M-learning flipped classroom proved effective in enhancing interest and mathematical concept understanding.